2022
DOI: 10.1155/2022/1543604
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Role of Platelet‐Rich Plasma Gel in Promoting Wound Healing Based on Medical Images of Wounds

Abstract: A wound is the pathological change of soft tissue under normal skin caused by various factors, such as collision, contusion, hot crush, avulsion, corrosive chemicals, operations, excessive wound tension after operations, local pressure that cannot be relieved for a long time, liquid immersion, local infection, and rejection reactions caused by allogeneic substances. e skin itself or its underlying soft tissue loses its integrity and continuity, thus losing its normal physiological function. Medical image analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…The platelet-rich plasma (PRP) plus NPWT treatment (PRP + NPWT) is a relatively new and effective modality to treat chronic, difficult-to-heal wounds and tissue defects in recent years. [5][6][7] The authors' department also confirmed in their previous studies that this treatment modality was highly effective in treating DSWI patients, with a significant advantage over the NPWT performed alone. 8 PRP contains a small amount of plasma liquid, a few or no leukocytes, and PLTs that are higher than the average normal concentration in our blood (3 $ 10 times the normal baseline).…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…The platelet-rich plasma (PRP) plus NPWT treatment (PRP + NPWT) is a relatively new and effective modality to treat chronic, difficult-to-heal wounds and tissue defects in recent years. [5][6][7] The authors' department also confirmed in their previous studies that this treatment modality was highly effective in treating DSWI patients, with a significant advantage over the NPWT performed alone. 8 PRP contains a small amount of plasma liquid, a few or no leukocytes, and PLTs that are higher than the average normal concentration in our blood (3 $ 10 times the normal baseline).…”
Section: Introductionsupporting
confidence: 53%
“…However, if SSWI is left to deteriorate, it would turn into DSWI which would easily affect a wound that will not heal for a long period and is difficult to treat, resulting in an elevated mortality rate. The platelet‐rich plasma (PRP) plus NPWT treatment (PRP + NPWT) is a relatively new and effective modality to treat chronic, difficult‐to‐heal wounds and tissue defects in recent years 5‐7 . The authors' department also confirmed in their previous studies that this treatment modality was highly effective in treating DSWI patients, with a significant advantage over the NPWT performed alone 8…”
Section: Introductionmentioning
confidence: 67%
“…Following an assessment of 1467 pertinent examinations, 13 studies released between 2009 and 2023 were included in the meta‐analysis since they matched the criteria for inclusion 13–25 . Table 2 summarizes the findings of these investigations.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen examinations from 2009 to 2023 were enrolled for the present meta‐analysis comprising 808 people with BWs in the study's starting point: 413 of them were using PRP and 395 were using standard therapy. The sample size was 25 to 100 subjects 13–25 . The examined data revealed that PRP had a significantly shorter healing time, a higher healing rate, a higher healed area percent and a higher graft take area percent compared with standard therapy in patients with BW.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation